Sistem Rekomendasi Pemilihan Nutrisi Hewan dengan Metode Content Based Filtering - Andrian Setya Putra; Pipin Widyaningsih; Sri Sumarlinda (Jurnal Inotera, 2024)
In this digital age, technology can make everyday life easier, including finding and providing food for livestock and pets. Hilda Pakan Supplier is a business that provides various types of nutrition, such as feed, vitamins, and veterinary medicine. At the time of observation, some customers were often confused in determining the right feed, vitamins, or medicine for their animals due to the lack of information they had. Customers usually have to ask the shopkeeper, which can take a long time especially when the shop is crowded. To overcome these problems, the purpose of this project is to use the content-based filtering method to create a recommendation system for animal nutrition choices. This method was chosen because the recommendation process is simpler and does not require rating data from other users. The system can provide recommendations in accordance with the needs and preferences of animals. In its application, the cosine similarity algorithm is used to measure product similarity based on text descriptions. The results show that this recommendation system is able to produce 10 products with the highest similarity value, which is 0.331060048. In the future, this system can be further developed by adding more products to provide more accurate insurance results.